Antibiotics and antimicrobial resistance - Karadjova, Dafina (Department of Anaesthesia and Reanimation, Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, R.N. Macedonia, 2020)
Man and the microbial world have had coexistence since the beginning of the world. But while some bacteria are able to establish a symbiotic balance with humans by providing a protective and stabilizing effect on the body, other bacteria attack and grow in human tissues causing disease. An antibiotic is a type of antimicrobial substance active against bacteria and the most im- portant agent for fighting bacterial infections. Antibiotics have been used since ancient times, but they caused a real revolution in the medicine in the 20th century. Proper classification and adequate understanding of how antibiotics work is especially important in the healthcare delivery process, and the use of antibiotics should always rely on the overall intended benefit, taking into account the adverse side effects. On the other hand, the effectiveness and easy access to antibiotics have led to their overuse, and thus the emergence of resistance. Antimicrobial resistance is defined as the resistance of a microorganism to an antimicrobial drug that was once able to treat an infection with that micro- organism. Resistance is a property of the microbe, not of a person or other organism infected with a microbe. Antimicrobial resistance is an ever-increasing public health problem worldwide. The low rate of detection of new antibiotics, together with the rapid spread of drug-resistant bacterial pathogens, is causing a global health crisis. The rate of resistance to bacterial pathogens is growing rapidly in both intensive care units, despite advances in modern medicine and intensive care. Infections caused by these resistant pathogens are difficult to treat and are associated to increased morbidity, mortality and cost. Hence, in this review we will consider the classification of antibiotics, their mechanism of action, with special emphasis on the mechanism of bacterial resistance.